Pengaruh Perencanaan Pajak dan Beban Pajak Tangguhan terhadap Manajemen Laba pada Perusahaan Subsektor Makanan dan Minuman yang Terdaftar di ISSI - Nurul Fatihah; Ramadhani Irma Tripalupi; Ridwan Effendi (EKALAYA : Jurnal Ekonomi Akuntansi, 2025)
This study was conducted based on many companies that practice earnings management in Indonesia. A company manipulates its financial statements by adjusting the figures in the financial statements using accounting policies so that the company looks good to external parties. This study aims to determine the effect of tax planning and deferred tax expenses on earnings management in food and beverage companies listed on the Indonesian Sharia Stock Index (ISSI) from 2020 to 2023, both partially and simultaneously. This study is quantitative in nature, which the researcher used to examine the predetermined sample. This study uses purposive sampling in selecting samples, namely by setting certain criteria so that 10 company samples were obtained as research objects. The results of the testing in this thesis simultaneously show that tax planning and deferred tax expenses have a significant effect on earnings management of 20.1%, while the rest is influenced by other factors not examined in this study. Meanwhile, partially, tax planning has an effect on earnings management, and deferred tax expenses do not have an effect on earnings management.